Procedure For Managing Dangerous Goods Permit Letters For Mv. Integra Vessel At PT. Karana Line Shipping Belawan Branch - Hambali Hambali; Dafid Ginting; Lilis Lilis (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
To find out more about how the shipping company PT. Pelayaran Karana Line Belawan carries out activities in the procedure for managing dangerous goods permits, especially the Medan Belawan Branch, starting from marketing providing information according to data that there is a dangerous goods load that will be loaded on the ship, then the operational party or external service makes a letter of application that will be given to the relevant agency, namely the Belawan Main Harbor Master's Office. Every permit management requires costs. The costs incurred will go into the State Treasury, namely Non Tax State Revenue (PNBP).